Assessing the global burden of interstitial lung disease and pulmonary sarcoidosis using multiple statistical models: analysis and future projections - Luna Zhao; Yue Zhou; Yun Jia; Lang Wang; Ye Liu; Guizhen Lv; Yihao Zhang; Jinyang Li; Junfeng Ren; Hongzheng Liu; Yufeng Zhang; Ning Wang; et al. (BMC Pulmonary Medicine)
Abstract Background Interstitial lung disease (ILD) and pulmonary sarcoidosis (PS) constitute major global health challenges, characterized by progressive respiratory symptoms and diverse epidemiological trends. Although the incidence and mortality rates of ILD and PS have increased following the COVID-19 pandemic, comprehensive research examining their burden and associated risk factors remains limited. Therefore, the present study aimed to analyze the spatiotemporal distribution, gender-specific and age-related disparities, and sociodemographic determinants of ILD and PS from 1990 to 2021 to facilitate evidence-based targeted interventions. Methods By using data from the Global Burden of Disease 2021 database, we analyzed age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and age-standardized disability-adjusted life year rate (ASDR) across 204 countries/regions. Temporal trends were evaluated using average annual percentage change (AAPC), age-period-cohort (APC), and Bayesian APC (BAPC) models. Decomposition analysis and Pearson’s correlation analysis were conducted to assess the impact of aging, population growth, and sociodemographic index (SDI). Joinpoint regression was used to identify inflection points in trends. Future disease burdens (2021–2050) were projected through BAPC modeling. Results Global ILD and PS cases increased from 157,441.17 in 1990 to 390,267.11 in 2021, with an annual increase in ASIR, ASMR, and ASDR by 0.61%, 1.32%, and 0.83%, respectively. High-SDI regions exhibited the highest ASIR (71.4/100,000) and ASMR (25.5/100,000). Males exhibited greater disease burdens than females ASDR 57.79/100,000 vs. 39.49/100,000 in 2021), with a peak incidence in the 70–74 age group. SDI showed positive correlations with ASIR and ASMR, exhibiting U-shaped relationships in certain regions. Projections indicated stable ASMR but increasing ASIR and ASDR by 2050, particularly among males. Conclusions The global burden of ILD and PS has increased markedly since 1990, influenced by population aging, industrial development, and socioeconomic disparities. Prioritizing early screening (e.g., high-resolution computed tomography and serum biomarkers), minimizing environmental and occupational exposures, and implementing gender-/age-specific interventions are critical measures. Strengthening healthcare infrastructure in low-SDI regions and integrating advanced diagnostic technologies are crucial for reducing future disease burdens.